1988
DOI: 10.1159/000174410
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Assessment of Pulmonary Hypertension: A Simultaneous Echo-Doppler Hemodynamic Study

Abstract: Thirty patients with stable chronic obstructive lung disease (COLD) underwent an echo-Doppler examination before and during right heart catheterization. No statistically significant differences between observations for any of two-dimensional echo-Doppler parameters were found. The measurement of all parameters taken during the catheterization correlated better with mean pulmonary artery pressure (mPAP) than those taken before. This difference was most evident for the isovolumetric acceleration time (r = 0.71 b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…Also, Marangoni et al reported that there was an excellent correlation between the measurements of PAP by Doppler echocardiography and by invasive method. 16 In addition, invasive method in estimating PAP is a difficult and a traumatic procedure for the patients. Also, it was difficult to obtain the approval of patients, who were included in the study, for invasive procedure because of the above-mentioned reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Also, Marangoni et al reported that there was an excellent correlation between the measurements of PAP by Doppler echocardiography and by invasive method. 16 In addition, invasive method in estimating PAP is a difficult and a traumatic procedure for the patients. Also, it was difficult to obtain the approval of patients, who were included in the study, for invasive procedure because of the above-mentioned reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Estimated RVSP was obtained using the modified Bernoulli equation and was recorded as a continuous variable; PH was defined as a RVSP ≥ 40 mmHg 3,10,2426 . Sensitivity analyses were conducted in which PH was defined as a RVSP ≥ 36 mmHg and RVSP was treated as a continuous predictor of allograft failure 24 .…”
Section: Methodsmentioning
confidence: 99%
“…In the absence of right ventricular outflow obstruction or pulmonary stenosis, non-invasive determination of pulmonary artery pressure by Doppler echocardiography has been shown to be closely correlated with that measured on catheterization [9,10]. …”
Section: Methodsmentioning
confidence: 99%